PEMBUATAN KITOSAN DARI KULIT UDANG DENGAN EKSTRAKSI MENGGUNAKAN MICROWAVE - Ani Purwanti (Retii, 2021)
The research has been conducted to make chitosan from shrimp shell with extraction using microwave. Microwave is a source of energy for heating and as a catalyst in a chemical reaction. The use of microwaves has advantages, namely short processing time, energy efficiency, easy process control, and produces good quality results. Isolation of chitin is done through three stages, namely demineralization, deproteination, and deacetylation. The process of deacetylation of chitin was done by varying heating time 3, 7, 11, and 15 minutes and varying NaOH concentration 20%, 30%, 40%, and 50%. 1:20 (mass/volume) of chitin were mixed with NaOH at the stage of deacetylation. The mixture put into the apparatus microwave in constant temperature at 60oC. Chitosan was washed until neutral and then was dried in oven until the mass was constant. The characterization was carried out using the Fourier Transform Infrared (FTIR) instrument and then the degree of deacetylation was calculated. The results that showed the degree of deacetylation is 69,7954%, water content 1.90%, and ash content 0.16% was achieved at reaction time in 3 minutes and NaOH concentration in 50%. Keyword: Chitin, Chitosan, Microwave